Sendikasizyon Kredileri - (:unkn) unknown (My University, 2003)
0

Loan syndication are one of the most important fund resources in the international financial markets. These credits are extremely important for the economies of developing countries due to the lack of sufficient capital accumulation. Loan syndications have reached considerable amounts in the international financial markets. These credits have many advantages both for the money - lending creditors and borrowing financial institutions. In some cases, this credit method can be risky for financial institutions due to the exchange - rate risk. Some of our national banks have fallen into financial difficulties due to high levels of outside borrowing in the form loan syndication in Turkey recently and the use of these credits with the aim of creating short-positions combined with the high levels of devaluations and the change of exchange rate policy to free floating exchange rate system in Turkey last year.